A study on utilization of coal ash for construction materials - Rusdiansyah; Yasruddin, Yasruddin; Adriani, Adriani; Rahman, Fauzi (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
During coal combustion, steam power plants have fly and bottom ash as by-products. However, according to Indonesian Government Regulation No.104 of 2014 on the management of hazardous and toxic waste, both fly ash with B409 code and bottom ash with B410 code are categorized as level-2 hazardous and toxic materials. A material can be categorized as a level-2 dangerous and toxic material due to its contents, has a delayed effect, an indirect effect on humans and the environment, and has sub-chronic or chronic toxicity. One of the proposed solutions for this problem is to utilize fly ash and bottom ash as an added material or substitute material for paver blocks, concrete blocks, road curbs, and road bases. This study aimed to determine the right composition of fly ash and bottom ash on paver block, concrete block, road curb, and road base to meet the minimum requirements. This study is expected to confirm the utilization of coal ash material for construction materials. Based on the results, the coal ash material in the form of fly ash and bottom ash could be used as an added material or substitute material for paver blocks, concrete blocks, road curbs, and road bases. The composition of fly ash and bottom ash as construction materials have met SNI 03 - 0349 - 1989 requirements on compressive strength for class II (K-70) concrete quality, then Job Mix Formula K-250 which refers to SNI 03-2834-2000 for road curb, then SNI 03 - 0691 - 1996 on the compressive strength requirements for quality B concrete bricks for paver blocks and roadblocks.